CPAP effects on atherosclerotic plaques in patients with sleep-disordered breathing and coronary artery disease: The ENTERPRISE trial. Issue 1 (January 2019) - Dohi, Tomotaka; Kasai, Takatoshi; Endo, Hirohisa; Wada, Hideki; Yanagisawa, Naotake; Nojiri, Shuko; Funamizu, Takehiro; Shitara, Jun; Doi, Shinichiro; Kato, Yoshiteru; Okai, Iwao; Iwata, Hiroshi; et al.
Highlights: The ENTERPRISE study will evaluate the effects of CPAP on coronary plaque in SDB. Plaque regression/progression will be assessed with using serial near-infrared spectroscopy-intravascular ultrasound study. The results will provide new insights into CPAP for SDB and residual risk. Abstract: Background: Sleep-disordered breathing (SDB) is a novel cardiovascular risk factor. To date, the effects of continuous positive airway pressure (CPAP) on coronary plaque atheroma in SDB patients with coronary artery disease (CAD) have remained unclear. The CPAP Effects on Atherosclerotic Plaques in Patients with Sleep-Disordered Breathing and Coronary Artery Disease (ENTERPRISE) trial was designed to evaluate the effects of CPAP treatment in addition to optimal medical treatment on coronary plaque regression in SDB patients. Methods: This study is planned as a prospective, randomized, open-label, single-center study. The presence of SDB is defined as a 3% oxygen desaturation index (ODI) of ≥15 events/h as measured by nocturnal pulse oximetry. A total of 100 eligible SDB patients undergoing intravascular ultrasound (IVUS)-guided percutaneous coronary intervention will be randomly assigned to either CPAP as add-on therapy or no CPAP for SDB (1:1 ratio for CPAP vs. no CPAP). The intervention will consist of 12 months of CPAP treatment. The primary endpoint will be percentage changes in plaque atheroma volume of the non-culprit lesion segment as measured by IVUS. A specialist sleep cardiology team will carefully monitor patients receiving CPAP treatment in order to quickly detect and resolve problems, and to motivate patients to continue treatment. Conclusion: This study will provide novel information on the effects of SDB and its treatment with CPAP on coronary plaque stability with regard to secondary prevention of CAD.